Pemahaman Makna Hidup Dalam Perspektif Kesehatan Pada Lansia Di Panti Werdha - Lono Wijayanti; Siti Damawiyah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Background: Everyone would want to enjoy their old age in a healthy condition both physically and spiritually, but the fact is that old age is more synonymous with periods of decline in physical, mental, and human interest. Purpose: The purpose of this study is to Identify the description of understanding the meaning of life from a health perspective for the elderly at the Panti Griya Werdha Jambangan in Surabaya. Methods: This study is a quantitative study with a descriptive design. The population in this study were all the elderly who live in the home for the werdha Jambangan with a total of 60 elderly and the sample used was 56 respondents using simple random sampling. The variable in this study is the understanding of the meaning of life from a health perspective in the elderly. The data were analyzed with descriptive statistics and presented in a frequency distribution table. Results: The results showed that out of 56 elderly people at the Werdha Jambangan Nursing Home in Surabaya, 73.2% of the respondents were 60-74 years old, 73.2% were female, and most of them 55.4% had an understanding of the meaning of a moderate life. Conclusion: Getting an understanding of the meaning of life requires a long and continuous process. A person who already has an understanding of the meaning of his life will be more prosperous and happier in life.Key words: Understanding the meaning of life, health perspective, elderly